APLIKASI ANATES VERSI 4 DALAM MENGANALISIS BUTIR SOAL - Ani , Mirna Herawa Interdiana Candra Sari (Faktor Jurnal Ilmiah Kependidikan, 2014)
Abstract Activity analyze the grain problem is one obligation for each teacher, because every teacher should ultimately be able to provide information to the school or institution to students about how and to what extent mastery and ability learners who have achieved the materials and the skills of the eye subjects who had been given. Anates program can be used as a means of evaluating teachers in achieving the learning objectives. By using Anates, test analysis process will be easier, faster, and accurate. Anates has the following capabilities: (1) Calculate the scores (original and weighted), (2) Calculate the reliability of the test, (3) Grouping subjects into groups of superior / asor, (4) Calculate the distinguishing power, (5) Calculate the level of difficulty, (6) Calculate the correlation score points with a total score, and (7) Determine the quality of detractors. Keywords: Anates Version 4, Grain Problem, and evaluation